2011
DOI: 10.1097/bpo.0b013e31821ffb8d
|View full text |Cite
|
Sign up to set email alerts
|

Meniscus Tears in the Young Athlete

Abstract: Level III retrospective cohort series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 0 publications
2
35
0
1
Order By: Relevance
“…They also concluded that medial meniscal repairs were significantly more likely to fail than lateral meniscal repairs. Vanderhave et al23) compared 31 cases of inside-out meniscal repairs with concomitant ACL reconstruction in young athletes with 14 cases of meniscal repairs without ACL reconstruction. Forty-three of the 45 patients showed excellent clinical outcomes at a mean of 27-month follow-up.…”
Section: Inside-out Repair Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…They also concluded that medial meniscal repairs were significantly more likely to fail than lateral meniscal repairs. Vanderhave et al23) compared 31 cases of inside-out meniscal repairs with concomitant ACL reconstruction in young athletes with 14 cases of meniscal repairs without ACL reconstruction. Forty-three of the 45 patients showed excellent clinical outcomes at a mean of 27-month follow-up.…”
Section: Inside-out Repair Techniquementioning
confidence: 99%
“…The indications for meniscal repair have remained controversial. However, the ideal indication for meniscal repair is an acute 1 to 2 cm longitudinal peripheral tear that can be repaired in conjunction with anterior cruciate ligament (ACL) reconstruction in young patients16,22,23,24). Nevertheless, some authors reported good clinical results after repair of meniscus tears extending into the avascular zone in patients less than 20 years of age25).…”
Section: Introductionmentioning
confidence: 99%
“…Meniscal ECM structure is intrinsic to its function, where circumferential collagen bundles develop to resist tensile hoop stresses [12, 13]. Tissue maturation is inversely related to the healing capacity of the meniscus, such that increasing patient age is correlated with worse clinical outcomes, including higher rates of repair failure [14, 15]. Importantly, patients over 40 with meniscal tears have fewer cells at the wound interface than younger patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increasing patient age correlates with worse clinical outcomes after meniscal repair, including higher rates of repair failure [30-33]. Importantly, patients >40 years of age with meniscal tears have significantly fewer meniscus cells at the wound interface than younger patients [34].…”
Section: Impediments To Meniscus Repairmentioning
confidence: 99%